Design and Internal Control of Consulting Company Project Activities - Afdol Muftiasa; Yumna Puspita; Lili Adi Wibowo; Agus Rahayu (Budapest International Research and Critics University, 2022)
In today's highly competitive market, efficiency and effectiveness are essential for a service business. Processes in the organization must be planned and controlled, which is why management must do both. Therefore, the purpose of this study is to describe and recommend improvements to the internal control system in a consulting firm. This study uses a qualitative methodology that includes an in-depth review of one of the leading IT service providers in Indonesia. Budget planning and reallocation for projects are two areas where the top management approval process does not meet adequate internal controls. This consulting company can use Application Systems and Products in data processing (SAP) to integrate their internal activity processes, as a result of the proposed improvements from this research. Due to their status as SAP consultants, the company's costs will be lower than the cost of developing a new system.